Evaluation of the benefits of micro credit: a study with reference to women beneficiaries in Idukki district - Jose, Sheena; M. Chockalingam, S (International Journal of Engineering and Technology, 2018)
Microcredit is a dominant instrument and a sensible attempt of nations to reduce poverty and boost up the development process. When the poor people particularly women get access to credit, they become economically powerful to improve themselves, their family, society as well as the entire nation. It is a revolutionary financial setup for poor people. The importance of microcredit has been proven and many countries adopt this as a powerful instrument to alleviate poverty. Empowerment is a multifaceted process of change which can be experienced by every individual in one way or the other. Financial support through the microcredit to women and their families play a vital task in empowering them. Women can enjoy non-economic benefits along with the economic benefits like increase of self-esteem, social recognition, decision making power, respect from relatives and society. It is necessary to promote many more microcredit schemes in different phases to uplift women to the main stream of life.In this scenario, this paper is an attempt to evaluate the effect of microcredit on women beneficiaries in terms of income generation and asset acquisition. The paper also focuses on how microcredit initiatives affect poor women in terms of economic empowerment and social recognition.